Electronic fetal monitoring, cerebral palsy, and medical ethics: Nonsense of a high order1. (March 2017) - Sartwelle, Thomas P.; Johnston, James C.; Arda, Berna
Electronic fetal monitoring (EFM) was predicted by its inventors to be the long-sought cerebral palsy (CP) nemesis. Rather than prevent CP or any other birth problems, 40 years of EFM use has done substantial harm to mothers and babies and created a worldwide CP-EFM litigation industry that enriches only trial lawyers. Physicians, frightened by the ever-expanding and costly CP-EFM litigation crisis, and focused on avoiding lawsuits at all costs, embraced ethical relativism—charitably called defensive medicine—and continued EFM use even in the face of overwhelming evidence that EFM is merely junk science. In doing so, physicians completely abandoned the bedrock bioethics principles of autonomy, beneficence, and nonmaleficence. This daily ethical drama has played itself out for the past almost half century with little protest from obstetricians and no protest from ethicists. This article reviews EFM harms, the CP-EFM litigation crisis, and the resulting abandonment of bioethics principles and explores why the CP-EFM paradigm has failed utterly to follow the Kuhnian model of the scientific, technology, medical paradigm shift.